LIFE SKILL HOME INDSUTRY MAKANAN TRADISONAL DAN STRETEGI PROMOSI DI PANGEAN KABUPATEN KUANTAN SINGINGI - Trismayanti, Ikis; Natuna, Daeng Ayub; Ahmad, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to look at the community?s ability to manage traditional food home based businesses and promotion strategies, this research was conducted in Pangean Kuantan Singingi district, variables used in life skills and promotion strategies, indicators of measurement in life skills, social skills, academic skills, vocational skills, measurement indicators in advertising promotion strategies, personal selling, publicity, sales promotion. The sample used in this study amounted to five respondents, the method used in this study was qualitative, the results obtained in this study were the skills in managing traditional food people never attended training, only yhe skill that existed in him. In marketing traditional food is fairly simple because it is only by word of mouth and markets directly to traditional markets and is entrusted to minimarkets around Pangean.Key Words: Life Skill, Promotion Strategy